2016
DOI: 10.1111/acel.12486
|View full text |Cite
|
Sign up to set email alerts
|

Does skeletal muscle have an ‘epi’‐memory? The role of epigenetics in nutritional programming, metabolic disease, aging and exercise

Abstract: SummarySkeletal muscle mass, quality and adaptability are fundamental in promoting muscle performance, maintaining metabolic function and supporting longevity and healthspan. Skeletal muscle is programmable and can ‘remember’ early‐life metabolic stimuli affecting its function in adult life. In this review, the authors pose the question as to whether skeletal muscle has an ‘epi’‐memory? Following an initial encounter with an environmental stimulus, we discuss the underlying molecular and epigenetic mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 186 publications
(223 reference statements)
5
120
1
1
Order By: Relevance
“…Of importance, in this study, a retention of DNA methylation of the myogenic regulatory factor, MyoD was evident over 30 population doublings in muscle cells that receive a single acute (24-h) cytokine stress in early life (24). This study, therefore, points to a potentially important epigenetic mechanism that underlies the susceptibility to loss of muscle mass (25). Furthermore, recent studies that investigated 44 musclespecific genes reported that where low methylation occurred, gene enhancer activity increased (26).…”
mentioning
confidence: 61%
“…Of importance, in this study, a retention of DNA methylation of the myogenic regulatory factor, MyoD was evident over 30 population doublings in muscle cells that receive a single acute (24-h) cytokine stress in early life (24). This study, therefore, points to a potentially important epigenetic mechanism that underlies the susceptibility to loss of muscle mass (25). Furthermore, recent studies that investigated 44 musclespecific genes reported that where low methylation occurred, gene enhancer activity increased (26).…”
mentioning
confidence: 61%
“…As comprehensively reviewed by Adam Sharples and colleagues, there is ample evidence that also SCs can retain a mitotically heritable “epi”‐memory of prior physical activity, metabolic challenges, as well as of prior maladaptive states (Sharples, Stewart, & Seaborne, 2016). SCs are indispensable to promote muscle repair and regeneration, but their actual role(s) in adult skeletal muscle homeostasis and exercise adaptation is not comprehensively understood.…”
Section: Transcriptional Memory Enables Learning From Experiencementioning
confidence: 99%
“…These environmentally regulated modifications of DNA and histones impact transcriptional control by altering spatial accessibility of DNA and chromatin structure, as well as recruitment of histone-modifying factors. Epigenetic programming is impacted by both acute and chronic exercise and central to skeletal muscle metabolic regulatory control (Howlett and McGee 2016) and maintenance of skeletal muscle mass with aging (Sharples et al 2016). DNA methylation is dramatically altered by exercise training in both human skeletal muscle (Nitert et al 2012) and adipose tissue (Ronn et al 2013).…”
Section: Genome and Epigenomementioning
confidence: 99%